The Role of the Gut Microbiome in Gastrointestinal Cancers: Gut Microbiome and Gastrointestinal Cancers - Sabri, Salam; Saeed Esmaeili-Mahani; Ahmed Majeed Al-Shammari; Khalid Jaber Kadhum luti; Mehdi Abbasnejad (Iraqi Journal of Cancer and Medical Genetics, 2024)
Cancer is a deadly malignancy of high clinical importance and remains one of the leading causes of death worldwide. Current conventional treatments for cancer include surgery, anticancer drugs, and radiation therapy. Resection surgery is the main treatment method but has a high recurrence rate. The human gut microbiome plays a crucial role in regulating various host processes, such as metabolism, inflammation, and immune and cellular responses. Moreover, it is becoming increasingly clear that the microbiome may also impact cancer development. The gut microbiota is a key component of the human microbial community, characterized by the highest number of bacteria and the greatest diversity compared to microbiomes in other parts of the body. The gastrointestinal tract (GI) extends through our natural environment, providing a suitable habitat and abundant nutrition for the microbiota. Gastrointestinal cancer encompasses a complex group of disorders and heterogeneous diseases. Both environmental and genetic risk factors can convert normal tissue into precancerous lesions, leading to the development of malignant cells. Despite advances in cancer treatment, resistance to chemotherapy and radiation therapy continues to pose a significant challenge. This is particularly relevant in light of new diagnostic and therapeutic methods for gastrointestinal tumors, which increasingly involve various strains of probiotics used as dietary supplements. As proposed treatments, probiotics may significantly benefit cancer prevention and therapy. They can enhance the metabolism of the gut microbiota during chemotherapy, potentially reducing its toxic side effects. Consequently, the potential use of probiotics as an anticancer therapy has received considerable attention in recent years. Conclusion: Current review article concentrates on the ability of probiotics to inhibit antibiotic-resistant Helicobacter pylori. However, there is a lack of studies exploring inhibitory resistance in other contexts. Despite these gaps, probiotics show considerable promise in cancer treatment and in enhancing tumor immunity.